J Biomed Eng Med Devic 2019
DOI: 10.35248/2475-7586.19.4.139
|View full text |Cite
|
Sign up to set email alerts
|

Design Methodology of a Balloon Expandable Polymeric Stent

Abstract: In the present work, a finite element-based study is undertaken to evolve a design methodology for developing a polymeric stent. Design steps include (1) crimping a stent cut from a polymer tube having outer diameter of 3 mm to a crimped diameter of 1.6 mm, (2) crimping recoil, (3) deployment of crimped stent to 3.3 mm outer diameter, (4) expansion recoil (mimicking crimping and dilation process to treat a 3 mm inner diameter artery) and (5) recoil under pressure. Effect of stent geometry parameters such as cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Ahuja et al98 studied PLA/PCL (5%) fabricated the next generation of bioresorbable vascular stents (BVS). The developed PLA/PCL tubes were tested in the rat subcutaneous model (Figure 4) and their cell‐tissue interactions were characterized, specifically related to inflammatory response, angiogenesis and capsularization 98‐101 …”
Section: Biodegradable Pla/polymermentioning
confidence: 99%
“…Ahuja et al98 studied PLA/PCL (5%) fabricated the next generation of bioresorbable vascular stents (BVS). The developed PLA/PCL tubes were tested in the rat subcutaneous model (Figure 4) and their cell‐tissue interactions were characterized, specifically related to inflammatory response, angiogenesis and capsularization 98‐101 …”
Section: Biodegradable Pla/polymermentioning
confidence: 99%
“…Therefore, many researchers have proposed different polymeric stent designs based on radial strength, radial stiffness, recoil, foreshortening, maximum stresses, and strains. [37][38][39][40][41][42] In this study, Kumar et al 43 design was opted for cutting the composite and polymeric tubes on FSLM, as shown in Figure 2D.…”
Section: Stent Designmentioning
confidence: 99%
“…The design process aims to optimize the geometrical and material parameters providing the best compromise among all the requirements at issue (Bressloff et al, 2016). In-silico simulations have proved to be a valuable support tool during the design stage, investigating the impact of the involved parameters with a significant saving of money and time with respect to a similar experimental procedure (Kumar et al, 2019), providing additional levels of detail, and expanding the analyses to scenarios resembling in-vivo conditions (Karanasiou et al, 2017;Morlacchi and Migliavacca, 2013;Roy et al, 2012). However, concerning innovative design, the efforts needed to implement and validate the numerical model may not be negligible, and the analyses of each variable impact may be quite expensive.…”
Section: Introductionmentioning
confidence: 99%